Successful Resolution of Preretinal Haemorrhage with Intravitreal Ranibizumab - Baharuddin Noorlaila; Embong Zunaina; Mohd-Noor Raja-Azmi (Case Reports in Ophthalmological Medicine)
We would like to report two cases of preretinal haemorrhage from two different aetiology courses of bleeding being treated with intravitreal ranibizumab and its outcome. Our first case was a 39-year-old man with a diagnosis of severe aplastic anaemia that presented with bilateral premacular haemorrhages in both eyes. His right eye vision was 6/45 and it was counting finger in the left eye. He was treated with intravitreal ranibizumab once to the right eye and twice to the left eye. Right eye showed complete resolution of premacular haemorrhage and minimal residual premacular haemorrhage in the left eye at 3 months after initial presentation. Our second case was a 32-year-old healthy teacher that presented with preretinal haemorrhage at superotemporal region extending to macular area in left eye secondary to valsalva retinopathy. Her left vision was counting finger. She was treated with single intravitreal ranibizumab to the left eye. There was significant reduction of premacular haemorrhage and her left eye vision improved to 6/6 at 10 weeks after injection. Both cases had favourable outcome with intravitreal ranibizumab and can be considered as nonsurgical treatment option in treating premacular haemorrhage.